The relevancy of the relevance: Different aspects of relevancy during emotional episodes evaluations - Dalit Milshtein; Jamalat Badarneh; Avishai Henik (Acta Psychologica)
The present research investigates the effect of relevance on our subjective experience while generating alternative events in our mind. To accomplish this aim, we asked participants to read and visualize 280 situations outlined in concise scripts. During each trial, they evaluated the relevance of the situation and other aspects of their metacognitive and emotional experience using a Likert scale ranging from 1 to 9. We employ PLS-SEM (partial least squares structural equation modelling) to investigate a potential causal sequence among three tiers of latent components. Specifically, the situational level consists of relevancy and plausibility factors, the metacognitive level consists of an imaginability factor, and the subjective experience level consists of feeling and thought suppression factors. Our analysis indicates that the effect of the plausibility of alternative scenarios on subjective experience is mediated by both the relevance and imageability factors, regardless of whether events are negative or positive. Furthermore, we successfully replicated the negativity rejection bias shown in our prior work. This bias refers to the tendency of participants to perceive bad events as less likely to occur than good events, independent of the precise details of those events.